Continued high mortality following diagnosis of HIV-associated Kaposi sarcoma in East Africa in the “Treat All” antiretroviral therapy era ― 2021-2024 - Helen Byakwaga; Aggrey Semeere; Megan Wenger; Esther Freeman; Miriam Laker-Oketta; Elyne Rotich; Beatrice P. Mushi; Matthew Ssemakadde; Hilda Muwando; Bronia Mwine; Racheal Ayanga; Celestine Lagat; et al. (BMC Cancer, 2026)
Abstract Background Stage at time of diagnosis and survival after diagnosis are critical parameters regarding control of any cancer in any geographical setting. In earlier research focusing on the initial years of the “Treat All” era (2016–2019), we found that HIV-associated Kaposi sarcoma (KS) in East Africa continued to be diagnosed at advanced stage of disease and conferred high mortality. Given the potential for broader implementation of “Treat All” as well as the announcement of National Comprehensive Cancer Network guidelines for cancer treatment in Africa since 2020 — but also the countervailing influence of the COVID-19 pandemic — we sought to provide an update on KS stage at diagnosis and survival after KS diagnosis among people living with HIV (PLWH) in East Africa. Methods We evaluated adult PLWH in Kenya, Tanzania, and Uganda with a new diagnosis of KS identified at ambulatory and inpatient settings in four regions between September 2021 and April 2024. At time of biopsy, participants were examined to document the extent of KS, and we used the AIDS Clinical Trials Group (ACTG) criteria for KS staging. In a prospective cohort design, we followed participants to monitor vital status. Results Among 493 PLWH with a new diagnosis of KS, the median (IQR) number of anatomic sites with KS lesions was 9 (4–12), and 91% had ACTG stage T1 (advanced KS). Over a median follow-up of 11 (IQR: 2.2–20) months, a total of 209 participants died, and three were lost to follow-up. Cumulative incidence of death (95% confidence interval) at months, 3, 6, 12 and 18 following KS diagnosis was 26% (22% to 30%), 32% (28%-36%), 39% (34%-43%) and 45% (40%-51%), respectively. Cumulative incidence of death was similar between countries and year of KS diagnosis. Conclusions Among PLWH with newly diagnosed KS in East Africa during the post-initial phase of the “Treat All” era (2021–2024), the majority had advanced disease at KS diagnosis and survival was very poor. These parameters are unchanged from the five prior years. Our findings emphasize the need for better KS control strategies in the region, including primary prevention, novel approaches for earlier detection, more timely linkage to care, and more accessible and potent anti-KS therapy.